Comparative Analysis of Bellman-Ford and Dijkstra Algorithms to Determine the Shortest Tourist Path in Central Lombok - Krissinta Bulan Wardhani; Gusti Yoga Nanda Karang; Septi Fajria; Muhammad Imam Al Paqih; Rida Akausar Hardi; M. Setyo Nugroho; Mamika ujianita Romdhini (Jurnal Pariwisata Nusantara (JUWITA), 2025)
Purpose: Central Lombok Regency has many tourist attractions spread out, which often makes it difficult for tourists to determine the best travel route to visit several locations at once. Choosing the shortest route is an important factor because it can save time, energy, and fuel costs, especially in tourist trips with unstructured schedules. Therefore, an effective method is needed to determine the shortest route to improve the efficiency of tourist trips. This study analyzes the shortest route to tourist attractions in Central Lombok Regency using two popular graph algorithms, including Dijkstra Algorithm and Bellman-Ford Algorithms Method: In this study, the data used are 6 tourist attractions in Central Lombok Regency. Tourist attractions are represented by points on the graph. Then the edge represents the road connecting the tourist attractions and the weight represents the distance to each tourist attraction from a starting point. Then to determine the minimum shortest distance of each tourist attraction based on the graph, Dijkstra and Bellman-Ford algorithms are used. Result: The shortest path to tourist attractions in Central Lombok Regency is obtained based on the Dijkstra and Bellman-Ford Algorithms. Contribution: Through this analysis, the advantages and disadvantages of the two algorithms in the context of determining tourist routes in Central Lombok can be identified.